(untitled) (Journal of Medicine, 2012)
Background: The incidence of cerebrovascular disease increases with age and the number of stroke is projected to increase as the elderly population grows. With the advancement of the health status of the Bangladeshi people gradually the segment of elderly populations is increasing and thereby inviting many diseases which are due to aging process. Stroke occurs when blood vessels that carry blood to the brain suddenly blocked or burst, preventing blood flow to the brain. The most common cause of blood vessel blockages are thrombosis (a blood clot) or an embolism (floating clot). Blood clots may form in the arteries that are damaged by atherosclerosis . Atherosclerosis is an aging process but some factors (risk factor) precipitate it to occur earlier. To find out the risk factors properly are of tremendous importance as risk factor change could directly influence or indirectly affect case fatality by altering the natural history of the disease. Serum lipids are thought to interact with the pathogenesis of stroke through atherosclerotic mechanism. As we the Bangladeshi people lives on rice mainly which is a carbohydrate food and we also usually do not practice regular exercise, so, though there is no clear statistical data but it can be presumed that serum lipids (cholesterol and triglyceride) of our people may be relatively in higher range and consequently we are gradually progressing to suffer from this fatal disease. Objectives: To identify the high serum lipid as an independent risk factor of stroke. Methods: This is a hospital based case-control study. Fifty (50) cases of stroke patients and age, sex matched 50 healthy control subjects were enrolled by non-random sampling. 12 hours fasting plasma lipids were estimated in both cases and control subjects. Then it was compared between cases and controls. Results: Hypercholesterolemia (raise of serum total cholesterol) was higher in case group than control (mean value 206 & 195.2 mg/dl respectively) but not statistically significant (>0.05). Mean LDL- cholesterol and triglycerides were significantly (P<0.05) higher in case group than control group (130.0mg/dl, to 106.3mg/dl & 230.7mg/dl, to 173.9mg/dl respectively). Mean value of serum HDL-cholesterol was not significantly lower is case group than control group (44.68 & 45.5 mg/dl respectively). Conclusion: Serum lipids are significantly higher in ischaemic stroke patients than control group (LDL cholesterol and triglyceride). So, it may be an independent risk factor of ischeamic stroke. DOI: http://dx.doi.org/10.3329/jom.v13i1.10043 JOM 2012; 13(1): 22-26